2020
DOI: 10.24953/turkjped.2020.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Aortic balloon valvuloplasty and mid-term results in newborns: a single center experience

Abstract: Background and Objectives. Aortic balloon valvuloplasty (ABV) has become the first-line treatment for critical aortic valve stenosis in infants. We aimed to evaluate the short- and mid-term results of patients who underwent ABV during neonatal period, the factors affecting the success and complications of the procedure. Methods. We retrospectively examined 65 patients who underwent ABV during the neonatal period between 1998 and 2017. All hospital records including cardiac catheterization reports, echocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…A study reported that 12.3% of patients had no palpable pulse on discharge despite sufficient time for streptokinase and tissue plasminogen activator treatment. 3 In our cohort, we detected PFAO and well-developed collateral circulation using US imaging in 19(5.9%) patients at the end of the 12-week dual treatment.…”
Section: Discusionmentioning
confidence: 74%
See 1 more Smart Citation
“…A study reported that 12.3% of patients had no palpable pulse on discharge despite sufficient time for streptokinase and tissue plasminogen activator treatment. 3 In our cohort, we detected PFAO and well-developed collateral circulation using US imaging in 19(5.9%) patients at the end of the 12-week dual treatment.…”
Section: Discusionmentioning
confidence: 74%
“…Femoral arterial access (FAA) is challenging and even in experienced hands it can be a lengthy procedure in neonates and low-weight infants. [2][3][4]10,11 Previous studies have shown that ultrasound-guided vascular access (US-GVA) increases the success rate and first attempt success rate and decreases failure rate, number of attempts, vascular access time, and vascular arterial complications. 5,7,[10][11][12] Although the evidence level of US-GVA was classified as 1B for vessel cannulation in adults, no level of evidence has been reported for FAA in children.…”
mentioning
confidence: 99%
“…Varan et al ( 16) reported moderate and severe valve insufficiency in 17 patients (26.2%) after valvuloplasty in their series of 65 cases. In order to reduce postprocedural valve regurgitation, the postoperative pressure gradient should be reduced to 30-35 mmHg, and the balloon diameter should be chosen to be 0.8-0.9 times the aortic annulus (16). In the follow-up of our patients, it was observed that aortic valve regurgitation ranged from minimal to first degree.…”
Section: Discussionmentioning
confidence: 99%
“…Its frequency in neonates has been reported to be between 19 and 62%. [1][2][3] Previous studies have reported variables including younger age, lower weight, prolonged vessel access and procedure times, increased number of attempts, large sheath size, sheath exchange, interventional procedure, access technique, operator experience, activated clotting time <250 seconds, and the diameter of the femoral artery <3 mm for arterial occlusion as risk factors. 1,[4][5][6][7][8][9] Femoral arterial access is challenging, and even in experienced hands, it can be a lengthy procedure in neonates and low-weight infants.…”
mentioning
confidence: 99%
“…1,[4][5][6][7][8][9] Femoral arterial access is challenging, and even in experienced hands, it can be a lengthy procedure in neonates and low-weight infants. [2][3][4]10,11 Previous studies have shown that ultrasound-guided vascular access increases the success rate and first attempt success rate and decreases failure rate, number of attempts, vascular access time, and vascular arterial complications. 5,7,[10][11][12] Although the evidence level of ultrasound-guided vascular access was classified as 1B for vessel cannulation in adults, no level of evidence has been reported for femoral arterial access in children.…”
mentioning
confidence: 99%